2012
DOI: 10.1016/j.thromres.2012.08.300
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of venous thromboembolism is associated with genetic variation in heme oxygenase-1 in Blacks

Abstract: Background-Venous thromboembolism (VTE) affects as many as 1 in 1000 individuals in the United States. Although Blacks are disproportionately affected by VTE, few genetic risk factors have been identified in this population. The inducible heme oxygenase-1 (HMOX1) gene encodes a key cytoprotective enzyme with anti-inflammatory, antioxidant and anticoagulant activity acting in the vascular system. A (GT) n microsatellite located in the promoter of the HMOX1 gene influences the level of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Haplotype tagging SNP THSD7A rs2074597 explains part of the chromosomal 7p linkage peak [217]. In addition, an association between venous thromboembolism and genetic variation in HO-1 (HMOX1) [183,218], methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism [219], affected homocysteine levels, and plasminogen activator inhibitor-1(PAI-1) 4G/5G mutation [220]. Furthermore, studies have also associated thromboembolism with other pathophysiological conditions, such as inflammatory bowel disease (IBD) and glioma.…”
Section: Genetic Risk Factors and Venous Thrombosismentioning
confidence: 99%
“…Haplotype tagging SNP THSD7A rs2074597 explains part of the chromosomal 7p linkage peak [217]. In addition, an association between venous thromboembolism and genetic variation in HO-1 (HMOX1) [183,218], methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism [219], affected homocysteine levels, and plasminogen activator inhibitor-1(PAI-1) 4G/5G mutation [220]. Furthermore, studies have also associated thromboembolism with other pathophysiological conditions, such as inflammatory bowel disease (IBD) and glioma.…”
Section: Genetic Risk Factors and Venous Thrombosismentioning
confidence: 99%
“…The present study speculated that Ccl2, a downstream gene of Klf15, may be the key factor in the effects of Klf15 on DVT formation. A study of the relationship between Hmox1 and DVT was conducted by Bean et al (34) who identified a critical cytoprotective enzyme encoded by the inducible Hmox1 gene with anti-inflammatory, antioxidant and anticoagulant activities in the vascular system. A (GT)n microsatellite located in the promoter of the Hmox1 gene influences the level of the response.…”
Section: Discussionmentioning
confidence: 99%
“…However, preclinical and clinical data support the hypothesis that impared hmox-1 activity may increase the initial embolic load and reduce endogenous rate of resolution. [35,36]…”
Section: Discussionmentioning
confidence: 99%